The Main Problems in the Translation of the Poem (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article examines the main difficulties that translators face when translating poetry and suggests specific ways to overcome each of them. However, it is also worth noting that since each period, each nation, each culture solves the problems of poetry translation in its own way, it is still impossible to define strict standards of poetry translation. Many linguists have tried to find solutions that can be used in many cases of poetry translation. The article also discusses independent and subordinate approaches to poetry translation, and the translator always has to choose which one.